Pedagogical criticism as a criticism of pedagogy as institutional to know: resistances and schools machine war - Cárdenas López, Gustavo Adolfo (Rastros Rostros, 2020)
Purpose: The present work tries, in a first instance, to show the difficulties that the institutional pedagogy presents to give account of the events of rupture that take place in the institutional school and therefore, the necessity of a Pedagogical Criticism arises. Description: In this first work, we will talk about the context in which institutional pedagogy emerges, which is the paradigm of modernity, from there the inability of institutional pedagogy to observe and assess resistance configurations will be shown; and second, based on this difficulty, it will also be shown why the need for a pedagogical critique that, through a genealogical analysis of the school and the rupture practices that are built in it, can be in turn criticism of pedagogy as institutional knowledge, that is, criticism of the institutionality and the principle of permanence on which it is founded. Point of view: The transformation of education, thanks to the need to analyze, interpret and understand new contexts, requires carrying out a Pedagogical Critique that is capable of generating ruptures, resistance and war machines schools; to value them not for their permanence and durability but for their epheme- rality, their transience and poor durability. Conclusion: Institutional pedagogy, which is born with modernity, by its very institutional nature cannot account for the events of resistance and rupture that occur in the institution school, and that have the ability to configure war machine schools. Therefore, it is essential for the transformation of education, that a Pedagogical Critique be made that questions the entire educational project that emerged with modernity and that is tied to a civilizational project, to the State.